THE DEVELOPMENT OF FINANCIAL LITERACY BY PHENOMENAL BASED LEARNING FOR HIGH SCHOOL STUDENTS - Yongthaisong, Mutita; Uttaman, Achira; Kampetch, Jaruwan (Journal of Educational Review Faculty of Education in MCU, 2024)
This research aims to develop financial literacy using learning activities based on the phenomenon-based learning approach for high school students. Study the financial literacy behaviors of high school students to be used in developing teaching and learning activities through Action Research, following the Kemmis and McTaggart’s idea with research steps including (1) Planning, (2) Acting, (3) Observing, and (4) Reflecting. The research findings indicate that: Students who received learning activities based on the phenomenon-based learning approach showed significantly higher average scores in financial literacy after studying compared to before studying, with statistical significance at the .05 level. The average scores for all components of financial literacy, including (1) financial knowledge, (2) financial behavior tendencies, and (3) financial attitudes, were significantly higher after studying than before studying, with statistical significance at the .05 level. Students who received learning activities based on the phenomenon-based learning approach showed changes in financial literacy in descending order, namely financial behavior tendencies, financial attitudes, and financial knowledge. These changes in financial literacy for each component were as follows: (1) Financial knowledge had unclear changes, with a difference of 0.70 points between post-study and pre-study scores. (2) Financial behavior tendencies showed clear changes, with a difference of 2.20 points between post-study and pre-study scores. (3) Financial attitudes showed clear changes, with a difference of 1.63 points between post-study and pre-study scores.